Perpaduan antara Pandangan Ekonomi Kovensional Dengan Ekonomi Syariah Melahirkan Sebuah Paham Ekonomi Yang Baru Dari Sebuah Sistem Yang Telah Ada - Irawan Fakhrudin Mahalizikri (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2018)
Economic System Applicable When the singer pointed on mechanism Unit And The Decision Making Institutions Implementing the decision against analysis, consumption and distribution of high-income. Therefore, the Economic system is Something Important to the Economy. Country and Economic System because of different form factors Complex, ex ideology, belief systems, views Life, Environment geographical, political, social, cultural, and other. At this time there are various kinds of economic systems of countries in the world. Nevertheless, generally speaking, the economic system can be grouped into two poles, namely capitalism and socialism. Other systems such as the welfare state, state capitalism, market Socialisme, democratic socialism basically works on the frame of capitalism and socialism. However, since the collapse of the Soviet Union, socialism is considered to have fallen along with the collapse of the Soviet Union. In the context of this paper, the purpose of conventional economics is the economic system of capitalism that is still a strong economic system in the world. The potential that exists on earth is a facility for human welfare and the problems that arise in the face of the earth is a human responsibility to solve it. God gives His favour to men intangible something that just uses, but it provides the means, roads, resourceful and example to cultivate potential and existing facilities to meet their needs. In order to meet the needs of the human life course to collide with the interests of other humans that can cause a problem. How in order to read the opportunities that exist, how can resolve collisions that may arise, how to get up to something in the future, this requires education to be answered and give the right direction. Islam is a religion which provides a balance between personal interests and the interests of the people covering the fields of economic, social, political, and education. How does Islam provide signposts to the man to answer the problems of life? and how the combination of the capitalist system with the emergence of an economic system based on Syariah? and how blend between conventional economic views of the islamic economy with the birth of a new economic system of an existing?